Repetition priming effects dissociate between miniature eye movements and induced gamma‐band responses in the human electroencephalogram. Issue 3 (15th May 2013) - Hassler, Uwe; Friese, Uwe; Martens, Ulla; Trujillo‐Barreto, Nelson; Gruber, Thomas
Abstract The role of induced gamma‐band responses (iGBRs) in the human electroencephalogram (EEG) is a controversial topic. On the one hand, iGBRs have been associated with neuronal activity reflecting the (re‐)activation of cortical object representations. On the other hand, it was shown that miniature saccades (MSs) lead to high‐frequency artifacts in the EEG that can mimic cortical iGBRs. We recorded EEG and eye movements simultaneously while participants were engaged in a combined repetition priming and object recognition experiment. MS rates were mainly modulated by object familiarity in a time window from 100 to 300 ms after stimulus onset. In contrast, artifact‐corrected iGBRs were sensitive to object repetition and object familiarity in a prolonged time window. EEG source analyses revealed that stimulus repetitions modulated iGBRs in temporal and occipital cortex regions while familiarity was associated with activity in parieto‐occipital regions. These results are in line with neuroimaging studies employing functional magnetic resonance imaging or magnetoencephalography. We conclude that MSs reflect early mechanisms of visual perception while iGBRs mirror the activation of cortical networks representing a perceived object.